Persaingan Antar Organisasi - Fitria Amania; Dini Vientiany (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Inter-organizational is a complex and dynamic relationship that occurs between two or more organizations that have different goals and characteristics. Relationships between organizations can take the form of cooperation, competition, or even conflict, all of which can affect organizational performance. Collaboration between organizations can increase profits and efficiency in coordinating, increasing knowledge, and solving problems together. Meanwhile, conflict between organizations can have a negative impact if it cannot be resolved properly. Conflict can lead to long discussions without finding an agreement and lack of organizational priorities, which can hamper organizational performance. For example, role conflict in an organization can have a negative effect on employee performance if it cannot be resolved properly. In some cases, conflict can be resolved by developing the conflict into a positive challenge. For example, role conflict in the PT Asuransi Kredit Indonesia (Persero) organization can have a positive impact if it can be resolved by increasing employee awareness and involvement in decision making.In this research, we will examine how inter-organizational relationships can influence organizational performance and how inter-organizational conflict can be resolved to improve organizational performance. We will also examine how collaboration between organizations can increase efficiency and profits in coordinating and solving problems together.